Differential quantity of key bioactive compounds and their antioxidative potential in novel apple genotypes: A correlative study for potential therapeutics - Syed Mudassir Jeelani; Salwee Yasmin; Ashiq Hussain Lone; Javid Iqbal Mir; Mohammad Irfan; Vishal Dinkar; Wasim Hassan Raja; Sajad Un Nabi; Mahendra Kumar Verma; Geetika Malik; Om Chand Sharma (Heliyon)
Apples are among the most economically vital crops growing worldwide. The present study aimed to analyze the variation in the content of key bioactive principles and antioxidative potential of novel apple genotypes (developed through breeding techniques) along with their correlation for possible therapeutic insights. Using the HPLC method, the bioactive compounds of these apples were investigated, and their contribution to free radical scavenging activity by employing DPPH assay. HPLC analyses displayed concentration of bioactive compounds varies significantly among these genotypes with catechins, epicatechins, quercetin, and rutin were the key bioactive compounds. Principal Component Analysis results revealed a correlation between total phenolic content and antioxidative potential. It is also apparent that phenols are primary contributors to the antioxidant efficacy among the apple genotypes under investigation for potential therapeutic application. Besides, the study dispenses some valuable statistics for the production of novel apple genotypes having added phytochemicals for conventional and modern breeders.